(3cJGH aj Yde SjGSI GdNjd hYdGLGJ CeQGVgG hCOhjJgG Ydi bOQ GdcaGjIs
(3ChdgG (B:s
(3hHYO agPG cJGH ai Yde GdaQhSjI ddNjd hEeGQGJge hGdYdGeGJ GdLjOI hGdQOjI s
(3BNQgG (B:s
(3heKd gPG ai GdcJGHI ddQLaI GfJgi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3aQhSjI JjehQ (B11) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs